2009
DOI: 10.3168/jds.2008-1487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different oral rehydration solutions on abomasal conditions and the acid-base status of suckling calves

Abstract: The aim of the study was to investigate the influence of oral rehydration solutions (ORS) on milk clotting, abomasal pH, electrolyte concentrations, and osmolality, as well as on the acid-base status in blood of suckling calves, as treatment with ORS is the most common therapy of diarrhea in calves to correct dehydration and metabolic acidosis. Oral rehydration solutions are suspected to inhibit abomasal clotting of milk; however, it is recommended to continue feeding cow's milk or milk replacer (MR) to diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 18 publications
1
48
0
2
Order By: Relevance
“…In addition to ORS treatment, they should receive their milk meal which is necessary to maintain energy supply (Heath et al, 1989). Preparing ORS in milk or MR is an easy way for farmers to provide diarrheic calves with electrolytes without adverse effects (Bachmann et al, 2009;Goodell et al, 2012). Such milk-ORS-mixtures are hypertonic, and administering them should cause thirst.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ORS treatment, they should receive their milk meal which is necessary to maintain energy supply (Heath et al, 1989). Preparing ORS in milk or MR is an easy way for farmers to provide diarrheic calves with electrolytes without adverse effects (Bachmann et al, 2009;Goodell et al, 2012). Such milk-ORS-mixtures are hypertonic, and administering them should cause thirst.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the strong ion and simplified strong ion approaches have been criticized, several research groups have investigated quantitative acid‐base analysis in domestic animals and concluded that the strong ion approach provided a more comprehensive evaluation of acid‐base balance than application of the traditional Henderson‐Hasselbalch equation . A key question remains to be answered: does application of strong ion theory improve our ability to understand the mechanisms of acid‐base equilibrium in vivo and treat acid‐base disturbances?…”
mentioning
confidence: 99%
“…In contrast, the administration of ORS mixed in milk replacer did not impair milk clotting (Bachmann et al, , ; Kirchner et al, ).…”
Section: Discussionmentioning
confidence: 99%